Barriers and facilitators to implementing person-centred dementia care in long-term care facilities in Western and Asian countries: a scoping review - Xin Guan; A-min Duan; Gong-kai Xin; Gong-kai Xin; Jan Oyebode; Yu Liu (Frontiers in Psychiatry)
BackgroundThere is a gap between the principles of person-centred dementia care and their actual implementation. However, scoping reviews of the barriers and facilitators to implementing person-centred dementia care in long-term care facilities for Western countries and Asian countries are lacking.ObjectiveTo identify and compare the barriers and facilitators to implementing person-centred dementia care in long-term care facilities between Western and Asian countries.MethodsIn line with Arksey and O’Malley’s methodology, a scoping review was conducted and is reported following PRISMA-ScR guidelines. Nine English language databases and three Chinese databases were searched to identify qualitative and quantitative research studies published in English and Chinese. Thematic analysis was used to summarise and characterize the barriers and facilitators to implementing person-centred dementia care in long-term care facilities for Western and Asian countries.ResultsThirty-three studies were included. Over half were conducted in Western countries (n =20). Barriers and facilitators were grouped under four high level themes: Nursing and care staff factors, people living with dementia and family factors, organizational factors, and resource factors. Inadequate knowledge of person-centred care, staffing shortages, time constraints, and low wages were the principal barriers to implementing person-centred dementia care in both Western and Asian countries.ConclusionsThe findings indicate that staff encounter numerous obstacles and needs in implementing person-centred care for people living with dementia in long-term care settings. Educational levels of nursing staff in Western countries were generally higher compared to Asian countries. Additionally, work-related injuries and stigma associated with dementia care presented unique challenges for nursing staff in Asia and were not cited in Western studies. Conversely, family-related factors were more frequently and elaborately cited as influencing person-centred dementia care in Western long-term care facilities. Moreover, Asian studies identified a significant lack of educational training support for person-centred dementia care, as well as shortages in staffing and poor availability of personalized, home-like environments